TANGGUNG JAWAB PIDANA, PERDATA DAN ADMINISTRASI ASISTEN PERAWAT DALAM PELAYANAN KESEHATAN DESA SWADAYA - Clara Yunita Ina Ola; Khoirul Huda; Andika Persada Putera (Legality : Jurnal Ilmiah Hukum, 2017)
This study analyzes the accountability of nurse's assistant in performing health service practices of people in swadaya village. This research uses a statue approach and conceptual approach. The act of health service which is often given by nurse's assistant to people in swadaya village is one form of health service which is done outside of the authority that should be done by the authorities in accordance with the rules and applicable law. The unequal distribution of health workers necessitates the nurse's assistant in performing medical practice to perform medical action so that it requires clear legal protection. nurse's assistant in performing acts outside of their authority have legal responsibility. The results showed that nurse's assistant in doing the practice outside of its authority to people in swadaya village can be held accountable of criminal, civil and administrative law, therefore it is expected for the government to be able to create policies or regulations so that in the legislation can be explained about the protection of law and legality for nurse's assistant in swadaya village, so there is a legal force for nurse's assistant in doing health service.